Impact of hepatitis C virus eradication with direct-acting antivirals on glycidic metabolism - Jucéli Márcia Hendges Sparvoli; Antonio Cardoso Sparvoli; Samuel de Carvalho Dumith; Afonso Alexandre Pereira; Ana Luisa Machado de Paula; Laís Garcia; Vanusa Belarmino; Vanusa Pousada da Hora; Ana Maria Barral de Martínez; Carla Vitola Gonçalves (Archives of Endocrinology and Metabolism, 2023)
ABSTRACT Objective: To compare the glucose metabolism of patients with chronic hepatitis C virus infection treated with direct-acting antivirals (DAAs) in pretreatment and sustained viral response (SVR) periods. Materials and methods: This was an intervention pre-post study of 273 patients with chronic hepatitis C virus infection treated with DAAs from March 2018 to December 2019. Glycidic metabolism was evaluated through homeostasis model assessment (HOMA) – insulin resistance (IR) and HOMA-β indices and assessments of insulinemia and HbA1c levels. These parameters were analyzed with a T test by paired comparison of the means of the variables and Wilcoxon's test paired for the median; in the variables with an abnormal distribution, the Z score was generated for the mean in both the pretreatment and SVR periods. Statistical significance was considered at p ≤ 0.05. Results: Among 273 participants, 125 (45.8%) had prediabetes, and 50 (18.3%) had diabetes. In SVR, there was a significant increase in platelets, albumin, alkaline phosphatase, cholesterol and triglycerides and a significant decrease in aspartate aminotransferase, alanine aminotransferase, gamma GT and bilirubin. The HOMA-IR and HOMA-β indices increased in SVR from 1.95 to 2.29 (p = 0.087) and 71.20 to 82.60 (p = 0.001), respectively. Insulinemia increased from 7.60 μU/mL to 8.90 μU/mL (p = 0.011). HbA1c decreased from 5.6 to 5.4 (p < 0.001). Among patients with prediabetes and those with diabetes, the reduction in HbA1c values was significant (p = 0.006 and p = 0.026, respectively). Conclusion: SVR significantly impacts and leads to improvement in glucose metabolism in patients with chronic liver disease induced by hepatitis C virus.